Characterization of organophosphate pesticides in urine and home environment dust in an agricultural community. (17th February 2018) - Tamaro, Catherine M.; Smith, Marissa N.; Workman, Tomomi; Griffith, William C.; Thompson, Beti; Faustman, Elaine M.
Abstract: Context: Organophosphorus insecticides (OPs) have been used to control agricultural pests found in Washington state. Farmworkers (FW) have higher exposure to OP pesticides than non-farmworkers (NFW), and FW children may in turn have higher exposure than NFW children. Objective: To examine the association between the concentration in house dust of five OPs used commonly in pome fruit orchards and the concentration in urine of dialkylphosphate metabolites (DAP), in a cohort of Hispanic FW and NFW and their children. Methods: Parents and children participated in three data collection periods over the course of one year. Urine samples were evaluated for the DAPs characteristic of OP exposure, and dust from homes and vehicles was evaluated for intact OP residues. Results: Geometric mean (GM) concentrations of OPs in house and vehicle dust were higher in FW households than NFW households in all agricultural seasons. GM concentration of urinary DAPs was higher for children in FW households than NFW households. Discussion: Regression analysis found a positive association between OP residues in house dust and the children's urinary DAPs. Conclusions: To our knowledge, this study is the first to report an association between pesticides in house dust and their biological metabolites in urine.